Lateral terrestrial water flow contribution to summer precipitation at continental scale – A comparison between Europe and West Africa with WRF‐Hydro‐tag ensembles. Issue 5 (19th May 2021) - Arnault, Joël; Fersch, Benjamin; Rummler, Thomas; Zhang, Zhenyu; Quenum, Gandome Mayeul; Wei, Jianhui; Graf, Maximilian; Laux, Patrick; Kunstmann, Harald
Abstract: It is well accepted that summer precipitation can be altered by soil moisture condition. Coupled land surface – atmospheric models have been routinely used to quantify soil moisture – precipitation feedback processes. However, most of the land surface models (LSMs) assume a vertical soil water transport and neglect lateral terrestrial water flow at the surface and in the subsurface, which potentially reduces the realism of the simulated soil moisture – precipitation feedback. In this study, the contribution of lateral terrestrial water flow to summer precipitation is assessed in two different climatic regions, Europe and West Africa, for the period June–September 2008. A version of the coupled atmospheric‐hydrological model WRF‐Hydro with an option to tag and trace land surface evaporation in the modelled atmosphere, named WRF‐Hydro‐tag, is employed. An ensemble of 30 simulations with terrestrial routing and 30 simulations without terrestrial routing is generated with random realizations of turbulent energy with the stochastic kinetic energy backscatter scheme, for both Europe and West Africa. The ensemble size allows to extract random noise from continental‐scale averaged modelled precipitation. It is found that lateral terrestrial water flow increases the relative contribution of land surface evaporation to precipitation by 3.6% in Europe and 5.6% in West Africa, which enhances a positive soil moisture – precipitation feedback and generates more uncertainty in modelled precipitation, as diagnosed by a slight increase in normalized ensemble spread. This study demonstrates the small but non‐negligible contribution of lateral terrestrial water flow to precipitation at continental scale. Abstract : Ensembles of coupled atmospheric ‐ hydrological simulations are presented for a summer season in Europe and West Africa. The model is enhanced with a water tagging procedure to evaluate the fate of land surface evaporation. The figure shows the change in continental precipitation recycling, that is the fraction of precipitation originating from land surface evaporation, induced by the consideration of lateral terrestrial water flow in the coupled simulations.